EFFECTIVENESS AND IMPROVE THE MORALE INFORMATION SERVICES FOR STUDENTS AT MTS MUHAMMADIYAH 10 KOTANOPAN ACADEMIC YEAR 2015-2016 - Anas Munandar Matondang (Ristekdik : Jurnal Bimbingan dan Konseling, 2016)
The study is based on the problem still lower students' knowledge of moral development in the school environment in general, the researchers are "Whether a student can understand the moral development through information services? Which is formulated as follows: Does the implementation of information services can be to boost the morale of students in MTs. Muhammadiyah 10 Kotanopan objective to be achieved is that students acquire an image of increased knowledge of the moral good in MTs. Muhammadiyah 10 Kotanopan. The method used is experimental research that will be used in the form of Pre Experiment Design with pretest-posttest Experiment Group Design. With a sample experimental class is class VII1 many as 26 students and classes that control VII2 class is 20 students. Information services conducted four meetings, the first meeting to implement the pretest and posttest implement all treatments. From the results of operations to be carried, there was a considerable improvement, especially the second meeting of the findings in the experimental group there were significant increases between posttest results. To test the hypothesis used by the formula Wilcoxon Signed Rank Test by using SPSS version 20 o'clock ujiwilcoxon used to analyze the results of observations from the two data are different or not. The average variable for understanding the moral development of 160.0769 (experiment) while 161.0500 (control) have seen a very significant difference. It is advisable for teachers to give students an understanding on the development of good morals in order to develop further, both in learning, implementation and evaluation of learning. For further research, is expected to make a research on moral development through other methods.